Doctors' stories, patients' stories: a narrative approach to teaching medical ethics. Issue 5 (October 1997) - Nicholas, B; Gillett, G
Abstract : Many senior doctors have had little in the way of formal ethics training, but express considerable interest in extending their education in this area. This paper is the report of an initiative in continuing medical education in which doctors were introduced to narrative ethics. We review the theoretical basis of narrative ethics, and the structure of and response to the two-day workshop.